Comprehensive Overview of the Brassinosteroid Biosynthesis Pathways: Substrates, Products, Inhibitors, and Connections - Bajguz, Andrzej; Chmur, Magdalena; Gruszka, Damian (Frontiers in Plant Science, 2020)
Brassinosteroids (BRs) as a class of steroid plant hormones participate in the regulation of numerous developmental processes, including root and shoot growth, vascular differentiation, fertility, flowering, and seed germination, as well as in responding to environmental stresses. During four decades of research, the BR biosynthetic pathways have been well studied with forward- and reverse genetics approaches. The free BRs contain 27, 28 and 29 carbons within their skeletal structure: 1): 5α-cholestane or 26-nor-24α-methyl-5α-cholestane for C27-BRs; 2) 24α-methyl-5α-cholestane, 24β-methyl-5α-cholestane or 24-methylene-5α-cholestane for C28-BRs; 3) 24α-ethyl-5α-cholestane, 24(Z)-ethylidene-5α-cholestane, 25-methyl-5α-campestane or 24-methylene-25-methyl-5α-cholestane for C29-BRs, as well as different kinds and orientations of oxygenated functions in A- and B-ring. These alkyl substituents are also common structural features of sterols. BRs are derived from sterols carrying the same side chain. The C27-BRs without substituent at C-24 are biosynthesized from cholesterol. The C28-BRs carrying either an α-methyl, β-methyl, or methylene group are derived from campesterol, 24-epicampesterol or 24-methylenecholesterol, respectively. The C29-BRs with an α-ethyl group are produced from sitosterol. Furthermore, the C29 BRs carrying methylene at C-24 and an additional methyl group at C-25 are derived from 24-methylene-25-methylcholesterol. Generally, BRs are biosynthesized via cycloartenol and cycloartanol dependent pathways. Till now, more than 17 compounds were characterized as inhibitors of the BR biosynthesis. For nine of the inhibitors (e.g., brassinazole and YCZ-18) a specific target reaction within the BR biosynthetic pathway has been identified. Therefore, the review highlights comprehensively recent advances in our understanding of the BR biosynthesis, sterol precursors, and dependencies between the C27-C28 and C28-C29 pathways.